2008
DOI: 10.3171/jns/2008/108/2/0365
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumor of the choroid plexus

Abstract: The authors report a case of inflammatory pseudotumor that developed in the choroid plexus of the lateral ventricle. The patient was a 73-year-old man who had undergone surgery for rectal cancer at another hospital 5 years earlier. He was referred to the authors' department, with his chief symptoms consisting of disorientation, right hemiparesis, and gait disorder that had gradually developed during the preceding month. On computed tomography and magnetic resonance imaging, a well-demarcated and homogeneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Xanthogranuloma, neurosarcoidosis, and low-grade astrocytoma are unlikely to bleed 2) . In previously reported cases of intraventricular pseudotumor, there also was no tumor bleeding [1][2][3]6,8) . However, in our case, repeated bleedings was characteristic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Xanthogranuloma, neurosarcoidosis, and low-grade astrocytoma are unlikely to bleed 2) . In previously reported cases of intraventricular pseudotumor, there also was no tumor bleeding [1][2][3]6,8) . However, in our case, repeated bleedings was characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory pseudotumor of the CNS is a condition often affecting young adults with a slight male preponderance 7) . Miyahara et al 6) reported that there have been only 5 case reports of inflammatory pseudotumor that developed in the choroid plexus (Table 1). In these cases, alterations in consciousness and contralateral hemiparesis were the initial symptoms, and the masses showed a contrast enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 9 cases of IP in the ventricles have been reported in detail (Table 1), 1,4,5,8,10,11,13,14) occurring in 2 females and 7 males aged 15-73 years (mean 49 years), indicating a tendency to occur in middle-aged or older men. 10) Eight of 9 cases developed in the lateral ventricle, with the remaining case developing in the fourth ventricle.…”
Section: Discussionmentioning
confidence: 99%